Recent Development Strategies of the Fur Farming Industry in Greece - Semos Nikolaos; Dotas Vasilios; Bampidis Vasilios (New Innovations in Economics, Business and Management Vol. 9, 2022)
In this work, a thorough research and study was carried out to determine the conditions prevailing in the breeding and operation of fur-bearing breeding units in Greece that are bred exclusively in the Region of Western Macedonia and to investigate development strategies of the sector. Particularly, all of the parameters that affect the effectiveness of breeding units were examined, and appropriate solutions to the fur industry’s difficulties and weaknesses were appraised and provided. The need for fur farms was prompted by the development of the fur clothing industry in the cities of Western Macedonia. The work focuses on industry practices and conditions from a technical standpoint, as well as the production process and development prospects through proposed strategies based on discoveries, literature, theoretical analyses, statistical analyses, and primary sources from direct personal connections. The overall conclusion of the work is that the fur industry will continue to develop dynamically, as everything points in that direction, and that this development will considerably help to the improvement of the living standards of the area’s residents.